RITUEL GESTUS: Kroppen som skala og som æstetisk form - Andersen, Jørgen Østergård (Tidsskriftet Antropologi, 1997)
Jørgen Østergård Andersen: Ritual Gestures. The Body as Scale and as Aesthetic Form The article focuses on ritual gestures, and it delineates a theoretical field of investigation, which gives expression to aesthetic practices, which are beyond - or rather, intersticial zones in - the semantic domains. It is argued that the ritual gestures generate a contact with a sphere, which is termed “sacred” in the anthropological tradition and “sublime” in the aesthetic, philosophical tradition. It is further argued that the aesthetic field cannot be reduced to the social order of semantic domains, since this would imply a misrepresentation of the meaning of ritual performances. The widespread contextual signification of rituals in anthropological debates and in ritual studies is therefore challenged in the article, and it is argued that such analyses do not give expression to the meaning or structure of the rituals. Such analysis, which merely describes the social context of the ritual, puts an end to the theoretical exploration into the singular meaning of the ritual - even before the analysis of the meaning gets under way. To illustrate these points, the ahjaliputa gesture is decribed and two “rites de passage” in Sri Lanka are analysed: kota hålu (giris puberty rituals) and upasampadå (monks higher ordination rituals). The subtitle - the body as scale and as aesthetic form - points to a further argument in the article that the body is a scale, which organises the semantic domains in a hierarchy of concrete, material objects. The aesthetic zones are found in such transitions from object to domain and they imply a transition from one scale to another. It is argued that the ambiguity of ritual gestures explores such intersticial zones.